BENEFITS OF CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) IN SECONDARY EDUCATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the key benefits of Content and Language IntegratedLearning (CLIL) in secondary education. CLIL is an innovative teaching approach thatintegrates foreign language learning with academic content, allowing students todevelop both linguistic and cognitive skills simultaneously. The paper highlights howCLIL enhances language competence, promotes higher-order thinking, increasesstudent motivation, and prepares learners for global communication. Furthermore, itdiscusses challenges teachers face in implementing CLIL, such as balancing contentand language objectives, and offers practical recommendations to overcome theseissues through professional training and collaboration. Overall, CLIL proves to be aneffective method for developing globally minded, competent, and motivated learners